2013
DOI: 10.1007/s00213-013-3388-y
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine exposure during adolescence: cognitive performance and brain gene expression in adult heterozygous reeler mice

Abstract: These findings support the hypothesis of pre-existing vulnerability (based on haploinsufficiency of reelin) to brain and behavioral disorders and regulative short- and long-term effects associated with nicotine modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 103 publications
(130 reference statements)
1
18
0
Order By: Relevance
“…While a complete summary is beyond the scope of this review, a number of papers have documented that adolescent nicotine results in persisting changes in signaling systems associated with synapses. Signaling systems with persisting changes include catecholaminergic (Trauth et al, 2001), serotonergic, and cholinergic systems , hippocampal and striatal cannabinoid CB1 and mu opiate receptors (Marco et al, 2007), adenylyl cyclase , and gene expression (Doura et al, 2008), including expression for reelin, GAD67, and BDNF (Romano et al, 2014). These may be merely associated with changes in robusticity of existing synapses, but these findings would also be consistent with the formation of new synapses.…”
Section: Adolescent Nicotine Synaptic Connectivity and Information mentioning
confidence: 93%
See 1 more Smart Citation
“…While a complete summary is beyond the scope of this review, a number of papers have documented that adolescent nicotine results in persisting changes in signaling systems associated with synapses. Signaling systems with persisting changes include catecholaminergic (Trauth et al, 2001), serotonergic, and cholinergic systems , hippocampal and striatal cannabinoid CB1 and mu opiate receptors (Marco et al, 2007), adenylyl cyclase , and gene expression (Doura et al, 2008), including expression for reelin, GAD67, and BDNF (Romano et al, 2014). These may be merely associated with changes in robusticity of existing synapses, but these findings would also be consistent with the formation of new synapses.…”
Section: Adolescent Nicotine Synaptic Connectivity and Information mentioning
confidence: 93%
“…Spaeth et al (2010) found impairments in contextual fear conditioning after adolescent nicotine, consistent with the DG cell changes we (Ehlinger et al, 2012) have found. Romano et al (2014) reported persistent modulation of cognition in mice, along with increased BDNF mRNA expression after adolescent nicotine. Mateos et al (2012) reported persisting effects on memory of adolescent nicotine (or a cannabinoid agonist), tested in the novel object test.…”
Section: Cognitionmentioning
confidence: 99%
“…Long term behavioral effects and molecular changes in brain mechanisms are resultant from nicotine exposure either through smoke or tobacco chewing. This is often evident and prominent in the adolescence humans (Romano et al, 2013). Depression is a characteristic long term behavior that may result from nicotine addiction (van der Meer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In adolescent heterozygous reeler mice, subchronic (6 day) nicotine free choice drinking ameliorates hyperlocomotion, perseverative behaviour and cognitive impairment [138,139]. Furthermore, in heterozygous reeler mice, subchronic nicotine restores mRNA levels of reelin and GAD67 in the cortex, hippocampus, striatum and cerebellum to WT-like levels [138,139]. Together, this suggests protective effects of subchronic nicotine in the heterozygous reeler mouse.…”
Section: Nicotinementioning
confidence: 95%
“…Reelin deficits have been observed in schizophrenia [132], and heterozygous reeler mice exhibit hyperlocomotion, PPI and cognitive deficits, and perseverative behaviour [133][134][135], as well as a loss of Purkinje cells of the cerebellum, which is also observed in patients with schizophrenia [136,137]. In adolescent heterozygous reeler mice, subchronic (6 day) nicotine free choice drinking ameliorates hyperlocomotion, perseverative behaviour and cognitive impairment [138,139]. Furthermore, in heterozygous reeler mice, subchronic nicotine restores mRNA levels of reelin and GAD67 in the cortex, hippocampus, striatum and cerebellum to WT-like levels [138,139].…”
Section: Nicotinementioning
confidence: 99%